The novel BET‐CBP/p300 dual inhibitor NEO2734 is active in SPOP mutant and wild‐type prostate cancer - Yuqian Yan; Jian Ma; Dejie Wang; Dong Lin; Xiaodong Pang; Shangqian Wang; Yu Zhao; Lei Shi; Hui Xue; Yunqian Pan; Jun Zhang; Claes Wahlestedt; et al. (EMBO Molecular Medicine)
Abstract CULLIN3‐based E3 ubiquitin ligase substrate‐binding adaptor gene SPOP is frequently mutated in prostate cancer (PCa). PCa harboring SPOP hotspot mutants (e.g., F133V) are resistant to BET inhibitors because of aberrant elevation of BET proteins. Here, we identified a previously unrecognized mutation Q165P at the edge of SPOP MATH domain in primary and metastatic PCa of a patient. The Q165P mutation causes structural changes in the MATH domain and impairs SPOP dimerization and substrate degradation. Different from F133V hotspot mutant tumors, Q165P mutant patient‐derived xenografts (PDXs) and organoids were modestly sensitive to the BET inhibitor JQ1. Accordingly, protein levels of AR, BRD4 and downstream effectors such as RAC1 and phosphorylated AKT were not robustly elevated in Q165P mutant cells as in F133V mutant cells. However, NEO2734, a novel dual inhibitor of BET and CBP/p300, is active in both hotspot mutant (F133V) and non‐hotspot mutant (Q165P) PCa cells in vitro and in vivo. These data provide a strong rationale to clinically investigate the anti‐cancer efficacy of NEO2734 in SPOP‐mutated PCa patients.